Quality of life in Indonesian conjunctival tumor patients - Indrakila, Senyum; Soewoto, Widyanti; Purnomo, Joko; Malindha, Erma; Asmara, Yusuf Vindra (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND As quality of life (QoL) research continues to expand, there remains a study gap of less common malignancies such as conjunctival tumors. This study aimed to investigate the differences in QoL between Indonesian patients with benign and malignant conjunctival tumors. METHODS This cross-sectional study was conducted from May–September 2024 and included 273 patients diagnosed with conjunctival tumors. The participants provided informed consent and completed the RAND SF-36 questionnaire to assess their QoL. A consecutive sampling method was employed to adequately represent benign and malignant tumor types. Data were analyzed using IBM SPSS version 26 to identify QoL differences among the patients. RESULTS This study found that squamous cell carcinoma was the most frequently observed conjunctival tumor, accounting for 28.9% of the cases. Patients with benign tumors had significantly higher QoL scores (69.61) than those with malignant tumors (43.05). Key factors influencing QoL included tumor type (p<0.001), age (p<0.001), sex (p = 0.039), occupation (p = 0.027), residence (p = 0.044), income (p = 0.010), and comorbidities (p = 0.045). CONCLUSIONS The results show significant disparities in QoL between patients with benign and malignant conjunctival tumors, emphasizing the impact of sociodemographic and tumor type on patient well-being. Focused healthcare plans are needed to help improve the QoL of patients with conjunctival tumors. Prioritizing early detection and providing complete support to enhance patient outcomes in Indonesia are crucial.